2015
DOI: 10.3892/or.2015.4451
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the miRNA, gene and pathway regulatory network in gastric cancer

Abstract: Gastric cancer is one of the most common malignant tumors worldwide; however, the efficacy of clinical treatment is limited. MicroRNAs (miRNAs) are a class of small non-coding RNAs that have been reported to play a key role in the development of cancer. They also provide novel candidates for targeted therapy. To date, in-depth studies on the molecular mechanisms of gastric cancer involving miRNAs are still absent. We previously reported that 5 miRNAs were identified as being significantly increased in gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…Identifying molecular causes of GC is of great importance in pattern recognition and therapeutic strategies. The poor prognosis of patients with GC primarily results from late detection, aggressive progression, poor response to available therapies and relapse (6,8,49). Therefore, in the present review, it was discussed how miRNAs are involved in the regulation of gastric CSCs and tumor environment through PTEN/PI3K/Akt signaling, which bears resemblance to the 'seed' and 'soil' in GC pathogenesis (91), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying molecular causes of GC is of great importance in pattern recognition and therapeutic strategies. The poor prognosis of patients with GC primarily results from late detection, aggressive progression, poor response to available therapies and relapse (6,8,49). Therefore, in the present review, it was discussed how miRNAs are involved in the regulation of gastric CSCs and tumor environment through PTEN/PI3K/Akt signaling, which bears resemblance to the 'seed' and 'soil' in GC pathogenesis (91), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) represent a large group of conserved small non-coding RNAs (ncRNAs) with a length of 17-25 nucleotides, which bind to the 3'-untranslated region (UTR) of mRNAs of their target genes, silencing expression by cleaving the mRNA molecules or inhibiting their translation (1,5). In this manner, ~30% human genes are modulated by miRNAs; the majority are directly or indirectly implicated in signaling pathways fundamental in cellular activities, including proliferation, differentiation, apoptosis and migration (7,8). As a result, miRNAs are crucial regulators in the initiation and progression of various diseases, particularly cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTLV-1 is a retrovirus which has been implicated in the occurrence of adult T-cell leukaemia and tropical spastic paraparesis. Zhang et al (2016b) also identified HTLV-1 signaling pathway in gastric cancer, but the role of HTLV-1 in gastric cancer still needs further study. Progesterone-mediated oocyte maturation is a nongenomic signaling mediated by steroids.…”
Section: Discussionmentioning
confidence: 97%
“…Regulating gene expression at the transcriptional level is the main function of miRNA; growing evidence indicates that miRNAs are abnormally expressed in various human cancers and they have significant effects on cancer progression and carcinogenesis [810]. As predicted by bioinformatic analyses, single miRNA has various targets; therefore, miRNAs are able to mediate numerous protein-coding genes and approximately one-third of human genes are regulated by miRNAs [11,12]. Among all miRNAs, down-regulated miR-145 has been observed in multiple types of cancers, including lung cancer [13], renal cell cancer [14], prostate cancer [15], bladder cancer [16], and colon cancer [17].…”
Section: Introductionmentioning
confidence: 99%